Supervisory behavior of primary school principals (Journal of the College of Basic Education, 2026)
The aim of this research is to identify the supervisory behavior of primary school teachers and to determine any statistically significant differences in supervisory behavior based on gender (male/female) and on years of service (1-5, 6-10, 11 and above). The study sample consisted of 300 male and female teachers. . The researchers developed a tool to measure supervisory behavior. The scale initially consisted of (48) items, and after establishing validity, applying statistical analysis to the items, and determining reliability, the scale in its final form consisted of (45) items. After the final application and using statistical methods, the results showed that the sample had a high level of supervisory behavior, and there was no difference according to the gender variable, and there was a difference in the years of service variable in favor of the category (11 and above). Based on the results, the researchers presented a number of recommendations and suggestions.